STUDY ON THE DEVELOPMENT OF CREATIVE ECONOMY-BASED DIVING TOURISM FROM A RECREATIONAL SPORTS PERSPECTIVE IN THE THOUSAND ISLANDS - Abdul Kholik; Zulham Zulham (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2026)
Kepulauan Seribu possesses significant potential for developing diving tourism as a recreational sport with immense economic value. This study analyzes the potential, strategies, and models for developing creative economy-based diving tourism from a recreational sports perspective in the Thousand Islands. Utilizing a qualitative descriptive method, data were collected through field observations, in-depth interviews with diving tourism stakeholders, recreational sports communities, policymakers, and documentation studies. The results reveal that diving tourism development relies on integrating creative economy sub-sectors, including dive guide services, digital content production, underwater photography, and experience based tourism packages. From a recreational sports perspective, diving tourism promotes physical activity, healthy lifestyles, and sustainable local business opportunities. However, challenges persist, such as limited instructor certification, inconsistent safety standards, suboptimal digital promotion, and environmental sustainability issues. This study recommends a pentahelix collaborative development model (government, academia, business, community, and media) to solidify the Thousand Islands as a premier diving destination within the sport tourism and creative economy frameworks. Ultimately, an integrated strategy empowers diving tourism to drive the local economy while fostering the sustainable development of recreational sports.